The Complaint System Based on Whistleblowing Concept and Message Digest 5 Cryptographic Method for Regency Inspectorate Office in Polewali Mandar - Qashlim, Akhmad; Mawar, Mawar; Assiddiq, Muhammad (Journal of Intelligent Computing & Health Informatics, 2021)
Inspectorate as an institution that supervises violations in government agencies or organizations. However, when individuals report a deviation, they often get into trouble because the identity of the reporter is not kept secret. So that in this research a complaint system is designed that uses the concept of whistleblowing with the cryptographic method. Where this method uses the Message Digest 5 (MD5) algorithm to lock or encrypt data so that the confidentiality of the reporting data can be maintained. In collecting data, it is done qualitatively, where data is collected through observation, interviews, and literature studies. This study resulted in a complaint system using the whistleblowing concept with the message digest 5 cryptographic method which was used at the Polewali Mandar Regency Inspectorate Office as a medium for reporting violations. With this complaint system, the reporter need not be afraid, because his identity will be encrypted using the Message Digest 5 algorithm.